Revolutionary Role of Clinical Pharmacist in Specialised Clinics: Professional Approach for Better Patient Care - James, Jude; Joseph, Jeeva; PS, Stephy; Abraham, Suja (Indian Journal of Pharmacy Practice)
The treatment associated economic burden of our country is rising at an alarming rate due to the prevalence of various disease conditions. Since the burden of disease and its management cost is increasing, India has got all reasons to be alarmed over matters of health. Without finding out and implementing newer alternatives to meet the health needs of the population, the present health system has to do more to come up with the struggles in order to provide the adequate healthcare services to get the desired outcome. Focussed or personalised care can be foreseen as a remedy and has been considered as a core component in achieving a sustained high quality health outcome. Specialised clinics devoted to an area of speciality aims at providing focussed or personalised care to the patient which enables to provide more medical attention to the patient by the involvement of multidisciplinary health professionals and is also cost effective. The specialised clinics plays a major role in timely follow ups to ensure that the patient gets the individualised optimal therapy.
Keywords: Clinical pharmacist; Specialised clinics; Focussed care; Patient care; Individualised therapy.